FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KECEMASAN LANJUT USIA DI PUSKESMAS JOHAR BARU II JAKARTA - Gerardina Sri Redjeki; Herniwaty Tambunan (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2019)
Anxiety is a manifestation of many different emotional processes, which take place when someone feels depressed or frustrated as well as other mental conflict. Other things that cause anxiety on elderly people are the presence of biological and psychological changes. The objective of this research is to get to know the factors pertaining to elderly anxiety at posyandu in the work region of Puskesmas at Johar Baru II Jakarta in 2017. Method of research: This research applies as correlative descriptive method with cross sectional approach. Samples as many as 114 elderly gained by using Krejcie table. The instrument used is the HRS-A questionnaire. The outcome of the research: by applying „ Kendall's tau-c test analysis, it was found that there is no significant relation between the age and elderly anxiety with p value = 0,307, there is a significant relation between family support and elderly anxiety with p value = 0,000, and social support and elderly anxiety with value p = 0,001. by using Chi Square test analysis showed that there is no significant relation between gender and elderly anxiety with value p = 0,680, and there is significant relation between physical condition and elderly anxiety with value p = 0.001. Discussion: Family support, social support as well as physical condition do influence on elderly anxiety, so hopefully by giving education to the elderly familly will prevent the anxiety on elderly, which will have an impact on the quality of life of the elderly.